Home, Belonging, and the Politics of Belonging in Mohsin Hamid's The Reluctant Fundamentalist - Karwan Tayeb; Aveen Ahmed-Sami (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ, 2021)
In the wake of 9/11, American fiction as well as the domains of the country's politics and media became permeated with binaries of us and them, self and the other. Mohsin Hamid's The Reluctant Fundamentalist challenges these notions and explores the questions of home and belonging, identification, the politics of belonging, and the constructions of boundaries. Similar to the discourse of postcolonial novels that are mainly concerned with writing back the margins to the center, The Reluctant Fundamentalist sheds light on the relegated matters related to the identity formation, power dynamics, belonging and the politics of belonging in the aftermath of 9/11. In her theory, Nira Yuval-Davis summarizes an investigative outline for the study of belonging and the politics of belonging. Yuval-Davis suggests three different investigative stages on which belonging must be studied: dealing with identity, social positions, feeling, political standards and ethics. She also explains the political projects, social divisions, and individual and collective identity narratives, all of which determine axes of power and power relations among people. This article explores how Hamid's The Reluctant Fundamentalist tackles the notions of home, belonging, and politics of belonging before and after the 9/11 events; how the novel renders the nationalist political projects of the US that aim at maintaining the boundaries of the community of belonging by the hegemonic political powers; and how these critical events and agendas influence the sense of belonging and perception of home among immigrants and citizens. The article is then concluded by stating that globalization has a great influence on individuals whether we favor the construction of boundaries driven by political projects that maintain nationalism and political communities or not. The theory of belonging and politics of belonging, defined by Nira Yuval-Davis, means that belonging has a tendency to become naturalized and ingrained in daily life. Only until it is challenged in some manner, it does become articulated, officially structured, and politicized. The politics of belonging consists of distinct political initiatives aiming at creating belonging to specific collectivities/ies, which are formed in very specific ways in these projects within extremely strict confines.